Factor Structure of an ICF-Based Measure of Activity and Participations for Adults in Taiwan's Disability Eligibility Determination System - Liao, Hua-Fang; Yen, Chia-Feng; Chiu, Tzu-Ying; Chi, Wen-Chou; Liou, Tsan-Hon; Chang, Ben-Sheng; Wu, Ting-Fang; Lu, Shu-Jen (Frontiers in Rehabilitation Sciences, 2022)
To assess Activity and Participation for adults in Taiwan’s Disability Eligibility Determination System (DEDS), we developed a measure, the Functioning Disability Evaluation Scale – Adult version (FUNDES-Adult), based on the 36-item interviewer-administered version of the WHO Disability Assessment Schedule 2.0. The purpose of this study was to examine the factor structures of performance and capability dimensions of the FUNDES-Adult. This study followed a methodology research design to investigate the construct validity of the two dimensions of the FUNDES-Adult. Two samples were randomly stratified from the databank of adults with disabilities to examine structural validity by the exploratory factor analysis (EFA, n=8730, mean age of 52.9±16.81) and the confirmatory factor analysis (CFA, n=500, mean age of 54.3±16.81). Results demonstrated that the EFA yielded 5-factor structures for both the performance dimension (73.5% variance explained) and the capability dimension (75.9 % variance explained). The CFA indicated that the second-order factor structures of both dimensions were more parsimonious with adequate fit indices (GFI, NFI, CFI, and TLI ≥ 0.95, RMSEA < 0.09). Results of this study provide evidence that the FUNDES-Adult has acceptable structural validity for use in Taiwan’s DEDS. Utility of the FUNDES-Adult in rehabilitation, employment, welfare, and long-term care services needs further study.